Working Memory Deficits in Multiple Sclerosis: An Overview of the Findings - Kouvatsou, Zoe; Masoura, Elvira; Kimiskidis, Vasilios (Frontiers in Psychology, 2022)
Although working memory (WM) and information processing speed (IPS) impairments in multiple sclerosis (MS) have been widely investigated, several questions, regarding the nature of these impairments and their relationship, remain unclear. The aim of this short communication article is to present an overview of our recent research findings regarding (a) the characteristics of WM impairment in MS patients and, more precisely, the degree of impairment observed in each WM’s component, i.e., phonological loop, visuospatial sketchpad, central executive, and episodic buffer and (b) the relationship between IPS and each of the four WM components, in an attempt to expand the existing rather narrow understanding of the interconnection between reduced IPS and WM impairment. Two studies of our research team are presented here and their findings are briefly discussed, highlighting the importance of further research on a specific component, namely the episodic buffer component among MS patients.